Can government think? : flexible economic opportunism and the pursuit of global competitiveness - Hartley, Kris (Routledge, Taylor & Francis Group, 2015)
"Climate change, financial crises, and other issues of global scale no longer concern only the developed world. The binding power of globalization has placed these challenges at the doorstep of almost every country, testing the evolutionary capacity of monolithic governance systems bound by institutional legacy and administrative stagnation. This book locates the concept of adaptive governance, used primarily in environmental management, within the context of economic policy. Introducing flexible economic opportunism, it argues that a particular style of institutional and administrative versatility enables innovative, evidence-based policy development."--